What do Cochrane systematic reviews say about the use of cannabinoids in clinical practice? - Latorraca, Carolina de Oliveira Cruz; Pacheco, Rafael Leite; Martimbianco, Ana Luiza Cabrera; Pachito, Daniela Vianna; Riera, Rachel (São Paulo Medical Journal, 2018)
BACKGROUND: The therapeutic effects of cannabinoid compounds have been the center of many inves- tigations. This study provides a synthesis on all Cochrane systematic reviews (SRs) that assessed the use of cannabinoids as a therapeutic approach. DESIGN AND SETTING: Review of SRs, conducted in the Discipline of Evidence-Based Medicine, Escola Paulista de Medicina (EPM), Universidade Federal de São Paulo (UNIFESP). METHODS: A broad search was conducted in the Cochrane Database of Systematic Reviews to retrieve any Cochrane SRs that assessed the efficacy and safety of cannabinoids as a therapeutic approach. The results and key characteristics of all reviews included were summarized and discussed. RESULTS: Eight SRs were included. They assessed the use of cannabinoids for the following types of con- ditions: neurological (two SRs), psychiatric (two SRs), rheumatological (one SR), infectious (one SR) and on- cological (two SRs). There was moderate-quality evidence showing that the use of cannabinoids reduced nausea and vomiting among adults, compared with placebo. Additionally, there was moderate-quality evidence showing that there was no difference between cannabinoids and prochlorperazine regarding the number of participants who reported vomiting, in this same population. CONCLUSIONS: This review identified eight Cochrane systematic reviews that provided evidence of un- known to moderate quality regarding the use of cannabinoids as a therapeutic intervention. Further stud- ies are still imperative for solid conclusions to be reached regarding practical recommendations.